The Vagina Dialogues: Genital Self‐Image and Communication with Physicians About Sexual Dysfunction and Dissatisfaction Among Jewish Patients in a Women's Health Clinic in Southern Israel. (24th September 2013) - Yulevitch, Aviva; Czamanski‐Cohen, Johanna; Segal, David; Ben‐Zion, Izhak; Kushnir, Talma
Abstract Introduction The health‐care system offers a variety of solutions for problems related to sexual dysfunction. To gain access to treatment options, women must be willing to discuss these issues with their physicians. Aim To examine the extent to which women discuss issues of sexual dysfunction with their physicians and to examine the contribution of aspects of sexual dysfunction, level of satisfaction, body image, and genital self‐image to their comfort with communicating with physicians about these issues. Methods One hundred ten secular‐appearing, Hebrew‐speaking Jewish women waiting for a routine gynecological appointment at a clinic in southern Israel responded to a self‐report questionnaire. Main Outcome Measures The Female Sexuality Function Index was used to assess sexual dysfunction, Gray's Modified Questionnaire to assess body image, and the Genital Self‐Image Scale to assess genital self‐image. We compiled a new measure to assess level of comfort in discussing sexual functioning and satisfaction with a physician. Results Forty‐four percent of the women had discussed sexual functioning issues with a gynecologist. Of those, 91.7% reported that the gynecologist initiated the discussion. The proportion of participants who would consult a gynecologist about sexual dysfunction was 74.5%, but only 41% would consult a family physician. Half of the women would expect a gynecologist to initiate such consultations, but only 20% would expect a family physician to do so. In a multivariate regression analysis, genital self‐image was the only significant predictor of women's comfort level with discussing sexual dysfunction with a gynecologist. Conclusions The respondents perceived the gynecologist, rather than the family physician, as an appropriate professional to consult regarding sexual dysfunction. However, they expected the gynecologist to initiate the discussion. Women with a positive genital self‐image are more comfortable in consulting about sexual dysfunction. Gynecologists should be made aware of their significant role in eliciting women's cooperation in such consultations and in contributing to improving women's genital perception. Yulevitch A, Czamanski‐Cohen J, Segal D, Ben‐Zion I, and Kushnir T. The vagina dialogues: Genital self‐image and communication with physicians about sexual dysfunction and dissatisfaction among Jewish patients in a women's health clinic in Southern Israel. J Sex Med 2013;10:3059–3068.